Pengaruh Budaya Organisasi Terhadap Kinerja Pegawai Pada Kejasaan Negeri Pesisir Selatan - Butar, Lusiana Butar; Yanti, Novi; Agussalim, Agussalim (Jurnal Riset dan Sains Ekonomi, 2025)
This research aims to analyse the influence of organisational culture on employee performance at the South Coast District Attorney's Office. Organisational culture in this study is measured based on the basic values of ASN ‘BerAKHLAK’ which include Service Orientation, Accountability, Competence, Harmony, Loyalty, Adaptability, and Collaboration. This study uses a quantitative approach with a survey method through a questionnaire distributed to 34 employees as a sample using total sampling technique. The results of the descriptive analysis show that organisational culture and employee performance are in the good category, with an average Respondent Achievement Level (RAL) of 83.92% and 83.53%, respectively. The dominant indicator in organisational culture is the Service-Oriented value, while in employee performance, it is the Feedback indicator. Based on the results of simple linear regression analysis, organisational culture has a positive and significant effect on employee performance, with a coefficient of determination (R²) of 0.829. This means that 82.9% of the variation in employee performance can be explained by organisational culture. The t-test also showed a significance value of 0.000 < 0.05 and a t-calculated value (12.477) > t-table (2.034), which reinforces this significant influence. This study highlights the importance of strengthening a service-oriented and collaborative organisational culture in efforts to improve employee performance in law enforcement agencies.